Surfactant induces ROS-mediated cell membrane permeabilization for the enhancement of mannatide production. (April 2020) - Wang, Le; Sha, Yu; Wu, Dapeng; Wei, Qixian; Chen, Di; Yang, Shuoye; Jia, Feng; Yuan, Qipeng; Han, Xiaoyao; Wang, Jinshui
Graphical abstract: Highlights: Surfactant-mediated permeabilization was beneficial to the mannatide bioconversion. Cetyltriethylammnonium bromide (CTAB) increased hydrophobicity and Zeta potential. The leakage of K +, Ca 2+ and the images of SEM indicated the disruption in membrane. The employment of CTAB induced the accumulation of ROS from 0.11% to 7.31%. The production of mannatide was increased by 98.6% compared to the untreated group. Abstract: A surfactant was a substance that had an important influence on the excretion of intracellular substances. In this work, it was found that cetyltrimethylammonium bromide (CTAB) inhibited cell viability but increased the mannatide production by optimizing the addition time. Results revealed that CTAB changed cell surface properties (cell surface hydrophobicity and Zeta potential was increased from 3% to 14% and −14.5 mV to −10.2 mV, respectively) and permeabilized cell membrane (intercellular ATP content was decreased from 28.599 μg/g to 9.737 μg/g while extracellular ATP content was increased from 33.051 μg/g to 82.809 μg/g; the concentrations of K + and Ca 2+ were increased to 3.9 mg/L and 2.1 mg/L, respectively; membrane potential was formed). Moreover, the images of scanning electron micrographs indicated distinct morphological changes and disruption on the surface of the cells. Further pyridinium iodides staining showed CTAB could induce cell apoptosis from 4.24% to 31% with increasing the relative intracellular reactive oxygen species (ROS) from 0.11% to 7.31%. It is the most noteworthy that the addition of CTAB increased the mannatide production to 1.46 g/L, 98.6% higher than that of untreated cells. Consequently, the utilization of CTAB for the preparation of mannatide provide theoretical foundation for the further large-scale production.